2019
DOI: 10.3390/atmos11010011
|View full text |Cite
|
Sign up to set email alerts
|

Change-Point Analysis of Precipitation and Drought Extremes in China over the Past 50 Years

Abstract: Increases in climate extremes and their impacts have attracted global attention recently. In this study, the change-point years of precipitation extremes (PEs) and drought extremes (DEs) were investigated by Moving t-Test at 500 stations across the six regions in China. The detailed temporal change processes of them were demonstrated by the cumulative deviation method based on the data from nine typical stations. The results showed that: 1) DEs were more significantly and widely increased than PEs, the station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Therefore, the insufficient total annual precipitation led to the Meanwhile, the distribution of the stations where the changepoint of increasing intensity in EAD occurred after 1984 was similar to that of stations with EAD frequency variation occurring after 1984. This analysis indicated that the number and distribution range of the stations with increasing EADs were less than those of the stations with increasing EDs [65]. However, the stations with increasing EADs and increasing EDs shared a similar change trend spatially.…”
Section: Case Study In the Nc Region (1) Yushe Countymentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, the insufficient total annual precipitation led to the Meanwhile, the distribution of the stations where the changepoint of increasing intensity in EAD occurred after 1984 was similar to that of stations with EAD frequency variation occurring after 1984. This analysis indicated that the number and distribution range of the stations with increasing EADs were less than those of the stations with increasing EDs [65]. However, the stations with increasing EADs and increasing EDs shared a similar change trend spatially.…”
Section: Case Study In the Nc Region (1) Yushe Countymentioning
confidence: 85%
“…Stations where the changepoint of increasing intensity in EAD occurred before 1984 were mainly distributed in Guangzhou, Guangxi, and Yunnan provinces (significant change-points), partial areas of Gansu and Ningxia provinces (significant change-points), and Shandong Province (insignificant change-point).Meanwhile, the distribution of the stations where the changepoint of increasing intensity in EAD occurred after 1984 was similar to that of stations with EAD frequency variation occurring after 1984. This analysis indicated that the number and distribution range of the stations with increasing EADs were less than those of the stations with increasing EDs[65]. However, the stations with increasing EADs and increasing EDs shared a similar change trend spatially.…”
mentioning
confidence: 85%
“…The nonstationarity in hydrometeorological variables, such as precipitation (Dhakal et al 2015;Gu et al 2019;Vu and Mishra, 2019), temperature (Aziz et al 2020;Carney et al 2020;Kärner, 2002), and drought index (Das et al 2020;Kwon and Lall, 2016;Wu et al 2020), has been extensively studied. Most of the existing research has focused on the long-term trends of hydrometeorological variables (Byakatonda et al 2018;Meshram et al 2017;Salman et al 2017) and on the change-points in these variables (Ahmadi et al 2018;Jiang et al 2019;Liu et al 2020). Such studies have discovered that, under the increasing influence of global warming, more high temperature events and extreme droughts have shown increasing trends of occurrence in the United States (Ge et al 2016), China (Ye et al 2019), Southeast Asia (Dong et al 2021), Australia (Sharples et al 2021), and Brazil (Geirinhas et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Climate trends and the current global warming have increased the frequency of drought events in the world by about threefold in the last 50 years [1]. As a result, the amount of land area affected by drought may reach 50% by the end of the century, and the frequency of extreme agricultural droughts events is projected to increase by about sixfold, with major drought events occurring every 5 years [2].…”
Section: Introductionmentioning
confidence: 99%